2013
DOI: 10.15580/gjas.2013.3.071113718
|View full text |Cite
|
Sign up to set email alerts
|

Assessment: Overview from Women Farmers in Anambra State, Nigeria

Abstract: The study assessed the needs of women farmers in Anambra State, Nigeria. A sample of 120 respondents who were randomly selected was used. Data were collected through interview schedule and analysed with percentage and mean scores. The results show that the women were middle aged (34%), fairly literate (36%), have household size of between 4-6 persons (61%) and have been in farming business for a period of between 10-19 years (45%). Information on climate change adaptation (M=3.4), information on climate change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Nigerian women despite their participation in agricultural development, it has been observed that they are faced with many problems (Bidemiet al, 2015). For instance, women access to the much needed farm productive resources have been identified to be very low due to marital, societal and religions reasons, lack of awareness caused by low literacy, lack of ownership and control of land, lack of sufficient and substantive collateral and inadequate knowledge of training in the use of improved innovations (Obiora, 2013;and Kughuret al, 2018). Additionally, it has also been reported that inadequate information about the improved technologies was one of the constraints in vegetable production (Alabiet al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nigerian women despite their participation in agricultural development, it has been observed that they are faced with many problems (Bidemiet al, 2015). For instance, women access to the much needed farm productive resources have been identified to be very low due to marital, societal and religions reasons, lack of awareness caused by low literacy, lack of ownership and control of land, lack of sufficient and substantive collateral and inadequate knowledge of training in the use of improved innovations (Obiora, 2013;and Kughuret al, 2018). Additionally, it has also been reported that inadequate information about the improved technologies was one of the constraints in vegetable production (Alabiet al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Women do not have adequate access to agricultural information and innovations (Bilkisuet al, 2016). Lack of separate land for women and inadequate contact with extension agents are serious constraints faced by women farmers (Obiora, 2013). Majority of the women use low yielding and unimproved planting materials, primitive and labour intensive farm implements, traditional farming practices, which have adversely affected agricultural production (Omeire, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, women make a large proportion of the agricultural labor force [1]. [2] argued that women account for 70 -80% of household food production in Sub-Sahara Africa. Women are employed in the agricultural sector predominantly as self-employed farmers, unpaid labor on family farms, and paid or unpaid workers on farms owned by others [3].…”
Section: Introductionmentioning
confidence: 99%